A Relevant Supply Chain Dashboard with Risk Management - Jellouli Olfa (International Journal of Supply Chain Management, 2023)
To have strategy actions, we need a dashboard and making the latter one is an easy action if we fixe relevant objectives. However, sometimes the dashboard is not composed of relevant performance indicators and we must study the risks linked to these latter. In fact, this is the objective of this article.